Revolutionary Politics and the Cuban Working Class - Zeitlin, Maurice (Princeton, NJ : Princeton University Press, 2015)
In 1962, the author got into Cuba and interviewed workers on the subject of the Revolution. Professor Zeitlin examines the effects of the revolution, and the influence of such factors as age, race, and skill on the workers' attitudes.Originally published in 1967.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Preface -- Contents -- Map -- 1. Orientations, Setting, Methods -- 2. Economic Insecurity and Politics -- 3. Race Relations and Politics -- 4. Skill and Politics -- 5. Sex and the Single Worker -- 6. Social Mobility and Politics -- 7. Social Relations in the Plant and in Politics -- 8. Alienation and Revolution -- 9. Political Generations -- 10. Revolutionary Workers and Individual Liberties -- 11. Revolutionary Politics and the Cuban Working Class -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Communism -- Cuba; Working class -- Political activity -- Cuba; POLITICAL SCIENCE / World / Caribbean & Latin American